Estimating moisture content and hydraulic properties of unsaturated sandy soils of Tiber River (Central Italy): integrating data from calibrated PR2/6 probe and hydraulic property estimator - Sofia Ortenzi; Martina Mangoni; Lucio Di Matteo (Acque Sotterranee, 2022)
The correct estimation of soil moisture data is essential in soil-water management and estimating the hydraulic properties of unsaturated soils. The increased use of Multi-Sensor Capacitance Probes (MCAPs) requires careful calibration. Without accurate calibration, the use of MCAPs leads to incorrect water content estimation, making them of no practical use. This work presents the specific calibration equations for the correct use of the PR2/6 profile probe on sands of different nature. As the iron oxides content of the Tiber River basin sands increases, the calibration lines slope increases, allowing the understanding of the different electromagnetic responses. As for other sands worldwide, sands with high iron oxides content show a relative high specific surface than quartz or calcareous sands, responsible for more adhesive water (e.g., high permittivity values). The water content data are integrated with a hydraulic property estimator allowing the estimation of the hydraulic conductivity of soils. Applying the manufacturer equation of the PR2/6 profile probe instead of the specific equation leads to an overestimation of the hydraulic conductivity values up to two orders of magnitude, making therefore rather incorrect the understanding of the phenomena occurring in the unsaturated zone.